Impact of Supply Chain Management Practices and ICT on Competitive Advantage and MSME Performance - Abdurahim, Muhammad Hasan; Kusmantini, Titik (Fakultas Ekonomi Universitas Garut, 2025)
MSMEs play an important role in the Indonesian economy, especially in the growing handicraft sector. However, many MSMEs face challenges in improving their competitive advantage and business performance. This study aims to analyze the influence of supply chain management practices and information and communication technology on competitive advantage and firm performance. This study uses a quantitative approach by distributing questionnaires to 109 MSMEs in the handicraft sector in Bantul and Sleman Regency. Data analysis was conducted using SEM-AMOS to see the relationship between variables. The results showed that supply chain management practices and the utilization of information and communication technology have a positive effect on competitive advantage and firm performance. In addition, the application of information and communication technology is proven to be able to improve supply chain efficiency, which has an impact on increasing competitive advantage and firm performance. Competitive advantage also acts as a mediating factor that strengthens the relationship between supply chain, ICT, and firm performance. These findings confirm that the integration of supply chain strategies with the utilization of digital technology can help MSMEs survive and thrive amid market competition.